Suplementação com ácidos graxos de cadeia média na emissão de metano, produção e qualidade do leite em vacas lactantes - Becker, Eduardo Garcia (2015)
Lipid additives used in the nutrition of dairy cows may affect both milk fat composition, as modifying the individual fatty acid profile, reducing methane emissions, becoming a sustainable practice for dairy cattle. To verify the effect of an additive based on medium chain fatty acids (MCFA) containing caproic acid, caprylic, capric, lauric and myristic, four treatments were tested: CTL (control without addition of MCFA), AGCM20 (5g MCFA), AGCM40 (10g MCFA) and AGCM80 (20g MCFA) on in vitro production gas (Experiment 1) and in the diet of lactating cows (Experiment 2). The bottles were distributed in a completely randomized design with repeated measurements over time and animals in triple latin square with four animals, four periods, four treatment, respectively. In Experiment 1 evaluated the production of gas, short chain fatty acids (SCFA) and methane (CH4); in Experiment 2 the productive parameters of milk and individual profile of fatty acids of milk fat. There was a significant decrease in gas production and methane (P<0.05), changing the profile of SCFA production in vitro treatment gas in AGCM40 and 80 compared with the control. No effects on productive parameters (P>0.05), however, were observed linear increase of C17:0 and C18: 3n6 (P<0.05) in the treatments AGCM20 and 80 respectively. It has been found that the use of MCFA 10 and 20g reduce the production of methane, without altering milk production and fatty acids of milk.